2017
DOI: 10.1016/j.chiabu.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A birth cohort study of Asian and Pacific Islander children reported for abuse or neglect by maternal nativity and ethnic origin

Abstract: Research identifying racial and ethnic disparities in child protective services (CPS) involvement in the U.S. has focused on the overrepresentation of Black children and the growing Latino child population. Little attention has been paid to children of Asian origin, the most underrepresented group of children in the U.S. CPS system. The objective of this analysis was to examine subgroup patterns of CPS involvement in California for Asian and Pacific Islander (API) children prospectively based on maternal nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(67 reference statements)
0
9
0
1
Order By: Relevance
“…Child maltreatment among AAPI families remains understudied (Finno-Velasquez et al, 2017 ; Hom, 2018 ). Although economic hardship and aggravation in parenting have been documented to lead to child maltreatment, they are not often explored as potential stressors that could lead to child maltreatment among AAPI families.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Child maltreatment among AAPI families remains understudied (Finno-Velasquez et al, 2017 ; Hom, 2018 ). Although economic hardship and aggravation in parenting have been documented to lead to child maltreatment, they are not often explored as potential stressors that could lead to child maltreatment among AAPI families.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the socio-demographic variables, this study included foreign-born status (Zhai & Gao, 2009 ) and family structure (Oliver et al, 2006 ) which were reported to be associated with child maltreatment. A prior study reported that fewer risks and lower CPS involvement rates were found among foreign-born mothers than US-born AAPI mothers (Finno-Velasquez et al, 2017 ). Additionally, relatively higher levels of aggravation in parenting were found among immigrant and minority families (Yu & Singh, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for child maltreatment: A large proportion of studies examined risk factors for child maltreatment. Several studies examined associations between maltreatment and maternal and perinatal risk factors, such as maternal marital status, maternal ethnicity, maternal age, maternal education level, engagement with prenatal care, smoking or substance use during pregnancy, alcohol or substance use after pregnancy, maternal experience of domestic violence or assault in the perinatal period, and maternal mental health disorders(Austin et al, 2018;Cant et al, 2019;Cram et al, 2015;Ekéus et al, 2004;Finno-Velasquez et al, 2017;Gessner et al, 2004; M. J Green et al, 2018;Hafekost, Lawrence, O'Leary, Bower, O'Donnell, et al, 2017;Högberg et al, 2019;Johnson-Motoyama et al, 2015;. Melissa O'Donnell et al, 2015;Orr et al, 2019;Parrish et al, 2011;Parrish & Gessner, 2010;.On an individual level, child characteristics examined included birth weight/small for gestational age(Boyd et al, 2019;Hafekost, Lawrence, O'Leary, Bower, O'Donnell, et al, 2017;Högberg et al, 2019;Kalland et al, 2006;Van Horne et al, 2018), birth defects(Van Horne et al, 2015, and diagnosis of ASD(McDonnell et al, 2019), Down Syndrome (Van Horne et al, 2018, or disabilities (e.g.…”
mentioning
confidence: 99%